The Effect of Product Diversification and Company Size on Company Profitability Case Study on UD Setya Abadi D.M - FATMAWATI, Vindi Atika; HARIYANA, Nanik (Integration: Journal Of Social Sciences And Culture, 2024)
Purpose: Product diversification is how a business can develop types of products both related to the central business and as substitutes and contemporary products. According to Ansoff (1957), diversification is related to product and quantity changes. This research aims to prove whether prodct diversification and company size increase profits so that business actors can decide on the proper steps in future business steps. Methodology: The method used in this research is multiple linear regression using the SPSS for Windows version 26 application. In this research, there are two independent variables and one dependent variable. The independent variable comprises product diversification and company size, while the dependent variable is company profitability. Findings: According to the data processing results using the multiple linear regression method, company profitability was positively influenced by product diversification and company size. Implication: Product diversification is carried out by adding product variants from a company and by requiring innovation that can differentiate one's product from other companies' products, which can place one's product above competitors' products.